Post-Pandemic Marketing Management Strategy Based on Fishbone Analysis in Kampung Inggris Pare, Kediri Regency (A Social Science and Entrepreneurship Journal, 2026)
This research was conducted to dig out the root causesof ineffectiveness of marketing strategies implementedin English Educational Tourism Village in Pare, KediriRegency and find the recommendations for them,specifically post- pandemic context. This research used aqualitative descriptive method, then, analyzed using afishbone diagram. The result depicted that Englishcourses in Pare, Kediri did not well implementmarketing strategies, specifically digitally. It wasbecause of lacking knowledge and skills regardingbusiness management, a lack of capital and lackinghigh-quality human resources. In general, researchersgave some recommendations for evaluating marketingstrategies such as: 1) Implementing Segmenting,Targeting, and Positioning (STP) strategies, 2) Digitalizingmarketing strategies 3) Gaining more capital, and 4)Upscaling human resource competencies.
Keywords: Marketing Management; Marketing Strategies; Post-Pandemi Qualitative Descriptive; Fishbone Diagram